The Influence of Social Media Use and Entrepreneurial Motivation on Entrepreneurship Interest among Lampung University Students - Tri Ananda, Kartika; Rouly Haratua, Dorothy; Husna, Nurul (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
Entrepreneurship is considered an important mechanism for improving the Indonesian economy through job creation, especially for young entrepreneurs, however, interest in entrepreneurship among young people, especially students, is still quite low, while in the current digital era, social media has become an important platform that influences the mindset and behavior of the younger generation, including in the context of entrepreneurship. For this reason, this research aims to analyze the influence of social media use and entrepreneurial motivation on interest in entrepreneurship among Lampung University students. The method used in this research is a quantitative approach, where data is collected through questionnaires distributed to 150 students from various departments at the University of Lampung. The data that has been collected is then analyzed using IBM SPSS version 25 software and testing the hypothesis using the t statistical test method. The results of this research support the hypothesis that has been established, namely that the use of social media has a significant positive effect on business resilience, and entrepreneurial motivation has a significant positive effect on entrepreneurship interest.